2018
DOI: 10.1021/jacs.7b12800
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Metal-Free Room-Temperature Phosphorescent Small Molecules with Multicolor Photoluminescence via a Host–Guest and Dual-Emission Strategy

Abstract: Metal-free room-temperature phosphorescence (RTP) materials offer unprecedented potentials for photoelectric and biochemical materials due to their unique advantages of long lifetime and low toxicity. However, the achievements of phosphorescence at ambient condition so far have been mainly focused on ordered crystal lattice or on embedding into rigid matrices, where the preparation process might bring out poor repeatability and limited application. In this research, a series of amorphous organic small molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
323
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 530 publications
(343 citation statements)
references
References 52 publications
(55 reference statements)
2
323
0
1
Order By: Relevance
“…Recently, pure organic room temperature phosphorescence (RTP) based emitters have attracted much attention as promising candidates for the white‐light emission . In general, the spin‐orbit coupling (SOC) in a pure organic material is too small to afford efficient ISC for the generation of triplet excitons.…”
Section: White‐light Emission Based On Single Organic Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, pure organic room temperature phosphorescence (RTP) based emitters have attracted much attention as promising candidates for the white‐light emission . In general, the spin‐orbit coupling (SOC) in a pure organic material is too small to afford efficient ISC for the generation of triplet excitons.…”
Section: White‐light Emission Based On Single Organic Moleculesmentioning
confidence: 99%
“…The other is to suppress the nonradiative decay of triplet excitons. Heavy atoms (such as chlorine (Cl), bromine (Br), iodine (I) and deuterium substituents) and heteroatoms (nitrogen (N)) are commonly used to facilitate the effective ISC, which promotes the triplet emission to achieve RTP . There are two approaches to achieve the white‐light emission.…”
Section: White‐light Emission Based On Single Organic Moleculesmentioning
confidence: 99%
“…Recently,T ian and co-workers reported that efficient RTP from as eries of amorphous organic small-molecule compounds were obtained by modifying different phosphors onto b-cyclodextrin (b-CD). [39] These bromine-containing phosphor molecules were initially inefficient phosphorescence emitters, althoughe fficient RTP luminescence with decent quantum yields was obtained by modifying them onto b-CD. Strong intermolecular hydrogen bonds between the cyclodextrin derivatives restricts the vibration of phosphors and eliminates selfquenching and atmosphericO 2 quenching.…”
Section: Enhanced Rtp Through Intermolecular Hydrogen Bondingmentioning
confidence: 99%
“…An important contribution made by Ma and Tian et al. provides a general and applicable strategy to obtain amorphous organic molecules with efficient RTP emission by simply modifying phosphors onto β‐cyclodextrin (β‐CD) . The nonradiative decay processes and oxygen quenching have been significantly suppressed by the strong intermolecular hydrogen bonding between β‐CD derivatives.…”
Section: Methodsmentioning
confidence: 99%